2017
DOI: 10.1002/chem.201701952
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Group 11 Bismuth Sulfide Nanoparticles Using Bismuth Dithioates under Mild Conditions

Abstract: The formation of mixed-metal sulfides with the general structure AgBiS and Cu BiS by a simple two-step process utilizing bismuth dithiocarboxylates as Bi and S precursors is described. A sonochemical reaction of Bi O with six different aryl dithioic acids: dithiobenzoic acid (BDT-H), 4-methoxydithiobenzoic acid (4-MBDT-H), 3-methyldithiobenzoic acid (3-MBDT-H), 2-mesitylenedithioic acid (2-MDT-H), 4-fluorodithiobenzoic acid (4-FBDT-H), and 2-thiophenedithioic acid (2-TDT-H) resulted in the corresponding comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Generally, ternary Cu−Bi−S sulfides could be synthesized with reactive sintering method, solvothermal method, polyol route, chemical bath deposition method,, vacuum‐sealed solid state reaction, and colloidal hot‐injection method ,. The controllable synthesis of metal sulfide nanocrystals should be assistant by sorts of thio‐ligand precursors, which results in many efforts in developing new precursors for the semiconductor sulfide nanocrystal preparation . For example, Wang et al have reported a generalized strategy for the synthesis of seven ternary sulfides by using one‐pot method from single source of metal‐diethyl dithiocarbamate precursors .…”
Section: Introductionmentioning
confidence: 88%
“…Generally, ternary Cu−Bi−S sulfides could be synthesized with reactive sintering method, solvothermal method, polyol route, chemical bath deposition method,, vacuum‐sealed solid state reaction, and colloidal hot‐injection method ,. The controllable synthesis of metal sulfide nanocrystals should be assistant by sorts of thio‐ligand precursors, which results in many efforts in developing new precursors for the semiconductor sulfide nanocrystal preparation . For example, Wang et al have reported a generalized strategy for the synthesis of seven ternary sulfides by using one‐pot method from single source of metal‐diethyl dithiocarbamate precursors .…”
Section: Introductionmentioning
confidence: 88%
“…A small amount of hydroiodic acid (3 vol.%) was added to the precursor solution to improve the crystalline and morphological stability of the resulting materials. [21] Modification of the metal iodides with the sulfide dianion was achieved by introducing reactive bismuth(III) tris(4-methylbenzodithioate) (hereinafter, Bi(S 2 CAr) 3 ) [34] to the precursor solutions. This choice was motivated by the solubility of bismuth benzodithioates in various organic solvents and their ability to decompose to bismuth(III) sulfide at low temperature (100-150 °C) in air.…”
Section: Deposition and Sulfide-modification Of Silver Bismuth Iodide Filmsmentioning
confidence: 99%
“…Senevirathna 218 did a double conversion-Bi 2 O 3 was converted to the sulfide using aryldithioic acid and then to Cu 3 BiS 3 using CuCl. This formed agglomerated particles 70-80 nm in size.…”
Section: Chemical Conversion Reactions Applied To Nanoparticles Havinmentioning
confidence: 99%